Technological advances in the diagnosis and management of inherited optic neuropathies - John O. T. Britton; John O. T. Britton; Patrick Yu-Wai-Man; Patrick Yu-Wai-Man; Patrick Yu-Wai-Man; Patrick Yu-Wai-Man; Benson S. Chen; Benson S. Chen; Benson S. Chen (Frontiers in Neurology)
Preferential degeneration of retinal ganglion cells (RGCs) is a defining feature of the inherited optic neuropathies (IONs), a group of monogenic eye diseases predominately comprising Leber hereditary optic neuropathy (LHON) and autosomal dominant optic atrophy (DOA). Their pathogenesis is characterised by mitochondrial dysfunction, which causes loss of RGCs leading to irreversible vision loss. Although currently incurable, there are several emerging therapeutic avenues encompassing gene therapies, precision medicine strategies and neuroprotection. These are underscored by recent technological advances such as next-generation sequencing and improved disease modelling. In this review, we discuss these advances and the impact these will have on future diagnostic and treatment capabilities. We first focus on the clinical presentation and pathogenic mechanisms of LHON and DOA, followed by a discussion of emerging technology to facilitate diagnosis and treatment. We highlight the current unmet clinical demand of IONs, and the promise of current and future research developments.